2007
DOI: 10.1158/1078-0432.ccr-06-1668
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Specific Transcriptional Regulators as Early Predictors of Independent Prognostic Relevance in Resected Colorectal Cancer

Abstract: Purpose: Prognostic studies on transcription factors acting at specific promoter elements have never been done so far. However, in tumors with long necessary follow-up, such as colorectal cancer, early-risk predictors would be needed. The invasion-related gene u-PAR is regulated via an activator protein 2 (AP-2)/Sp1 (À152/À135) and an AP-1binding promoter motif (À190/ À171), mediating u-PAR induction by K-Ras and Src. The present study was done to give first evidence for early prognostic relevance of transcrip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 40 publications
1
25
1
1
Order By: Relevance
“…Together with our previously published report that Src activity and also cooperation of transcription factors and Src regulating u-PAR are indicators of poor prognosis in colorectal cancer patients (15,31), these results corroborate the notion that Src inhibition and, specifically, an inhibition of Srcinduced u-PAR gene expression mediated by phospho -c-Jun bound to AP-1 motif À190/À171 might be promising strategies to prevent tumor progression and metastasis in colorectal cancer, specifically by inhibiting the decisive initial metastatic steps of invasion and intravasation into the systemic circulation.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Together with our previously published report that Src activity and also cooperation of transcription factors and Src regulating u-PAR are indicators of poor prognosis in colorectal cancer patients (15,31), these results corroborate the notion that Src inhibition and, specifically, an inhibition of Srcinduced u-PAR gene expression mediated by phospho -c-Jun bound to AP-1 motif À190/À171 might be promising strategies to prevent tumor progression and metastasis in colorectal cancer, specifically by inhibiting the decisive initial metastatic steps of invasion and intravasation into the systemic circulation.…”
Section: Discussionsupporting
confidence: 68%
“…However, because in another recent publication we see a significant correlation of Src activity, AP-1 binding, and u-PAR protein in a larger patient series (n = 92; ref. 31), the most likely explanation for the lack of significance in the present paper is the small case number. Still, the significant correlation between Src and AP-1 and between u-PAR, Src, AP-1 and pN stage supports the in vivo relevance of our present work for colorectal cancer patients.…”
Section: Discussioncontrasting
confidence: 53%
“…Sp1 was present in 74.8% of colon cancer tissues examined in one series, compared with presence in 42.2% of the normal colonic mucosa examined, and was overexpressed in colonic cancer stem cells (16). Sp1 has also been identified as a prognostic indicator in colorectal cancers (17,18). Many established interactions of Sp1 with other proteins and enzymes involve post-translational modifications and include interactions with histone deacetylases (19).…”
mentioning
confidence: 98%
“…In general, the molecular mechanisms that control CRC progression are related to the altered expression of different proto-oncogenes, tumor suppressor genes, cytokines and their receptors, including Ras, Src, p27 kip1 , p16 ink4a , interleukin (IL) and the epidermal growth factor receptor (EGFR). [1][2][3][4][5][6][7] Notably, these abnormalities involve the signal transducers and activators of transcription (STAT) signaling pathway, specifically STAT3 and STAT5 signaling, although very few studies have reported the abnormal expression or activation of STAT proteins in colorectal cancer. 8 Understanding the molecular mechanisms of STATs may further the development of novel therapies targeted in CRC treatment.…”
mentioning
confidence: 99%